Participant Evaluation of Twelve-Step Group Linkage for Jailed Women With Alcohol Use Disorder - Schonbrun, Yael Chatav (International journal of offender therapy and comparative criminology, 2019)
Jailed women are an underserved population with elevated rates of alcohol use disorders. Brief jail stays make delivery of case management and traditional alcohol treatment impractical yet women face significant reentry challenges with few help resources. Accounting for these challenges, linking jailed women with a twelve-step program volunteer for a one-on-one meeting has been hypothesized to provide a means of support that can transition with women after jail discharge. In-jail meetings are theoretically consistent with the common twelve-step practice of conducting twelve-step calls. The acceptability and content of a one-on-one, in-jail meeting with a twelve-step volunteer were explored using qualitative data collected through interviews with 72 women directly following their in-jail volunteer meeting. Participants found the meeting to be acceptable and to contain many useful elements, and content was in line with the standard twelve-step calls. Findings are encouraging both for the potential utility of the intervention and for dissemination of similar linkage approaches.